MICRO ENVIRONMENT FEELING – MAINTAINER AND REFLECTOR OF THE LATGALIANS’ SYSTEM OF VALUES - Čakša, Valda (Via Latgalica, 2013)
The aim of the article is to describe the attitude of Latgalians towards the components of natural objects of their nearby residence space (micro environment) – mežs (forest) and prūds (pond), as well as the objects created by humans – ceļš (road), which to a certain extent confi rm the understanding of the objects close to the place of residence in daily life of the preceding generations of Latgalians, as well as allow to compare these insights to the manifestations of Latgalianness discovered in the discourses of today. Researchers of the geographical environment and identity defi ne space as a geometrical, topological, three-dimensional structure, in which the objects and their relationships interact with a subject (human). In the social and cultural background of each populated area and the structures typical to them maintain the carriers of the micro-environmental identity, interaction of which with the priorities of a human activity facilitates and maintains the comprehension of values. Within the process of interaction of several groups of factors are forming the spatial and - in a wider meaning - environmental identity of micro environmental objects, which is defined as a significant sub-structure of personal self-identity. The environmental psychologists are emphasising the importance of functional knowledge, which is developed by using ‘bad’ and ‘good’ experiences regarding some objects, places and spaces according to their capability to satisfy the biological, psychological, social and cultural needs. Thus the value systems within a framework of a specific community are influenced by the experience of application of environmental objects, while multiform functions of micro environmental objects are reflected in the ethic, aesthetic, cognitive, educative and other notions about themselves and society in general. The attitude towards the micro-environment reveals also the body of macro-environmental factors – social and economic, ecological, as well as geographical and spatial, which a person faces in his/her daily activity. Various studies on the Latgalian mentality, as well as language and culture carried out in the previous century, are highlighting that exactly the rural environment is the basis of a Latgalian person’s interest in the individual’s place in nature, and in great things – such as individual’s mission, identity, Latgalianness, responsibility for its preservation, etc. This identity is not separable from the recognition of belonging to some social unit. In its turn the closest surrounding or micro environment of a contemporary Latgalian consists of several segments, with which s/he is tightly linked: family members and their occupation, house, natural objects of the closest surrounding, neighbours and their occupation, objects of the social life and traditions, etc. New modern aspects are introduced in these segments by the involvement of regional population in political, cultural and scientific processes of the state. Since the first condition for formation and development of a personality is the entirety of action and personal relationship, ensuring the orientation in various community systems of relations and viewpoints, then through language joining of the system of values is taking place, recognized not only in the regional community, but also in the national country. Involvement on the state level circulations nowadays confirms not only possibilities of the Latgalians, but also creates new tendencies and opportunities in the understanding of Latgalianness and also in the position against the attitude of inhabitants of other counties and the national state towards all the Latgalic matters. Thus the personalities popular in the Latgalian society, by confirming the link among the historical and contemporary Latgalian identity tendencies, significance of micro-environmental phenomena in the daily communication of regional population, Latgalian identity and psychology, as well as culture maintenance and preservation topicality, facilitate the orientation of regional society socialization, maintain the power of intellect, civic position and through the kinds of public consciousness manifestations activate the issues of equal rights and perseverance of their own native language. Active involvement in the process of solving of the present economic, political, cultural, ecological, administrative, scientific, etc. national issues of Latvia makes modern society to consider the factors of Latgalianness and contemporary tendencies of the identity manifestations. If the insights that a personality of an individual is mainly formed by the inborn characterizers have dominated in the description of former generations then the present social advancement and contribution of an individual him/herself in the personal development (his/ her self-performance and socialization experience), his/her patriotism, feeling of the micro- environment of Latgale region as a component of the system of values comprehension is based mainly on the attitude towards four interrelated elements: 1) nature environment maintaining a certain order and equilibrium in the geographical space of Latgale and, by meeting the needs of a human economic activities and social life, simultaneously facilitates also the formation of a certain attitude towards the objects created by nature; 2) the environment created by human – houses, household buildings, towns, etc., that as places for concentration of the people make the corresponding infrastructure of the specific society’s standard of living to develop and to be maintained, by serving to meet the social, economical and cultural needs of the community members; 3) social environment formed by mutual relationship of the people in a community, region, country. Social environment reflects also the relationship with other communities (at the regional, state, international level), as well as the influence of scientific and technical achievements on the geographical environment of Latgale and the entire Latvia in general, meeting the political, social, economical, cultural, communication and other needs of a person; 4) internal environment is formed by the body of personal viewpoints of separate individuals – attitude towards cultural, economic, political, etc. ideas typical to the epoch and their implementation patterns (historical consciousness), making to revaluate their opportunities and making of a decision regarding an active or observing position. Thus the interaction of Latgalian micro-environment with the internal environment of a contemporary Latgalian person confirms not only him/her personality order at a physical, mental, emotional and intellectual level, but also forms the basis of social equilibrium and the most significant factor of the identity or the awareness of place belonging and choice of activity direction.